1998
DOI: 10.1302/0301-620x.80b5.0800924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particulate debris on macrophage-dependent fibroblast stimulation in coculture

Abstract: The interactions between the different cell types in periprosthetic tissue are still unclear. We used a non-contact coculture model to investigate the effects of polymethylmethacrylate (PMMA) particles and human macrophage-derived soluble mediators on fibroblast activation. Macrophages were either exposed or not exposed to phagocytosable PMMA particles, but fibroblasts were not. Increasing numbers of macrophages were tested in cocultures in which the fibroblast cell number was held constant and cultures of mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…43 A non-contact co-culture of macrophages and fibroblasts showed a marked increase of IL-1β and IL-6, but not of TNF-α release, compared with macrophages alone after exposure to polymethylmetachrylate particles. 41 Interestingly, this study showed a similar pattern to our findings in the monocyte/endothelial cell co-culture system. However, other co-culture studies with different agents, including particles, demonstrate absence of enhanced stimulation compared with mono-cultures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…43 A non-contact co-culture of macrophages and fibroblasts showed a marked increase of IL-1β and IL-6, but not of TNF-α release, compared with macrophages alone after exposure to polymethylmetachrylate particles. 41 Interestingly, this study showed a similar pattern to our findings in the monocyte/endothelial cell co-culture system. However, other co-culture studies with different agents, including particles, demonstrate absence of enhanced stimulation compared with mono-cultures.…”
Section: Discussionsupporting
confidence: 88%
“…36,40,41 Figure 2 shows the effect of exposure to silica for 43 h on the release of TNF-α, IL-1β, IL-6, and IL-8 from the mono-and cocultures. Figure 3 shows silica-induced release of IL-4, IL-10 and TGF-β from these cultures.…”
Section: Effect Of Silica In Co-and Mono-culturesmentioning
confidence: 99%
“…As the interleukin‐6 released by the gingival fibroblasts was essential for the augmentation of MMP‐1 expression by the macrophages, cross‐talk between the two types of cells exposed to high glucose was proposed by the authors. Another study, using co‐culture, found that the release of interleukin‐6 was increased 100‐fold when compared with that using culture of macrophages alone (30).…”
Section: Discussionmentioning
confidence: 99%
“…The release of macrophage chemoattractants from fibroblasts further supports the relationship and synergism that may occur between macrophages and fibroblasts in the periprosthetic membrane. Lind et al reported that fibroblasts and macrophages exposed to titanium particles in coculture increase the release of IL-6 by a 100-fold when compared to macrophage cultures alone [18]. Zickus et al reported increased production of MCP-1 and MIP-I alpha from fibroblast-macrophage cocultures as well [45].…”
Section: Discussionmentioning
confidence: 99%